People tracking in video - Lee, Euston Yousheng. (2013)
People tracking in video have been gaining popularity in recent years for both convenience purpose and security purposes. With the recent scare of terrorist attacks, many organisations have improved their security devices. Being able to track suspicious characters to their destinations many a times can save lives.